Understanding Behavioral Transformation of Resuscitative Subjects - Raghavendra Prasad, G. (International Journal of Psychosocial Rehabilitation, 2024)
Near Death Experience, it has been still a debatable phenomenon after so many research works done across the world. The scientific community is still harping about the phenomena and there is an extreme urge to unveil the relation of human behaviour with brain in cognitive resurgence occurring after the phenomena. There is also anexistential impulse to associate the relation between the cognitive restructuring, behavioural change and NearDeath Experience (NDE). The post recovery phases usually quoted as Post Traumatic Stress Disorder (PTSD) generally indicates the negative impact caused by phenomenon like NDE. In an attempt to understand the actual aftermath and the relation between behavioural change and NDE, the author is proposing a NDE- Mixed-Method Design Protocol (NMDP). The protocol will be helpful in understanding and establishing the cognitive resurrection happening in the brains of NDErs and the repercussion of the phenomenon through a combination of Qualitative and Quantitativeresearch techniques